Enhancing the Security of Customer Data in Cloud Environments Using a Novel Digital Fingerprinting Technique. (4th May 2016) - Chidambaram, Nithya; Raj, Pethuru; Thenmozhi, K.; Amirtharajan, Rengarajan
Abstract : With the rapid rise of the Internet and electronics in people's life, the data related to it has also undergone a mammoth increase in magnitude. The data which is stored in the cloud can be sensitive and at times needs a proper file storage system with a tough security algorithm. Whereas cloud is an open shareable elastic environment, it needs impenetrable and airtight security. This paper deals with furnishing a secure storage system for the above-mentioned purpose in the cloud. To become eligible to store data a user has to register with the cloud database. This prevents unauthorized access. The files stored in the cloud are encrypted with RSA algorithm and digital fingerprint for the same has been generated through MD5 message digest before storage. The RSA provides unreadability of data to anyone without the private key. MD5 makes it impossible for any changes on data to go unnoticed. After the application of RSA and MD5 before storage, the data becomes resistant to access or modifications by any third party and to intruders of cloud storage system. This application is tested in Amazon Elastic Compute Cloud Web Services.